2020
DOI: 10.31315/jta.v16i2.3985
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Biochar Tempurung Kelapa Dan Pupuk Kandang Sapi Terhadap Sifat Kimia Tanah Dan Produksi Tanaman Sawi Pada Tanah Pasir Pantai

Abstract: Tanah pasir pantai memiliki beberapa keterbatasan untuk budidaya tanaman. Biochar tempurung kelapa dan kotoran sapi merupakan bahan amelioran untuk memperbaiki keterbatasan di tanah pasir pantai. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh biochar tempurung kelapa dan kotoran sapi terhadap sifat kimia tanah dan produksi tanaman sawi di tanah pasir pantai. Penelitian dilakukan di Rumah Kaca Fakultas Pertanian Universitas Pembangunan Nasional “Veteran” Yogyakarta pada bulan Maret sampai Mei 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…The determination of the dose of six mycorrhizae spores plants was based on a previous study by Syamsiyah et al (2014), which demonstrated that the mycorrhizae dose of 5 g plant -1 showed the best results in paddy rice. The second factor was a soil ameliorant, without an ameliorant (S0), cow dung 60 tons ha −1 (S1) (Prasetyo, 2014), rock phosphate 150 kg ha −1 (S2), biochar 25 tons ha −1 (S3) (Rahayu, Saidi, et al, 2019), cow dung 60 tons ha −1 + rock phosphate 150 kg ha −1 (S4), cow dung 60 tons ha −1 + biochar 25 tons ha −1 (S5), and rock phosphate 150 kg ha −1 + biochar 25 tons ha −1 (S6). Each unit of the experiment was repeated three times so that there were 42 total polybags experimental units.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of the dose of six mycorrhizae spores plants was based on a previous study by Syamsiyah et al (2014), which demonstrated that the mycorrhizae dose of 5 g plant -1 showed the best results in paddy rice. The second factor was a soil ameliorant, without an ameliorant (S0), cow dung 60 tons ha −1 (S1) (Prasetyo, 2014), rock phosphate 150 kg ha −1 (S2), biochar 25 tons ha −1 (S3) (Rahayu, Saidi, et al, 2019), cow dung 60 tons ha −1 + rock phosphate 150 kg ha −1 (S4), cow dung 60 tons ha −1 + biochar 25 tons ha −1 (S5), and rock phosphate 150 kg ha −1 + biochar 25 tons ha −1 (S6). Each unit of the experiment was repeated three times so that there were 42 total polybags experimental units.…”
Section: Methodsmentioning
confidence: 99%
“…This soil possesses poor chemical and biological quality and becomes the limiting factor for plant growth. Sandy soil has low organic matter content, total nitrogen, and cation exchange capacity (CEC) (Rahayu, Saidi, et al, 2019;Zulkoni et al, 2020), which will lead to low fertility, water retention, and macro and micronutrient content (Yost & Hartemink, 2019). Its properties also do not provide support for microorganisms' life (Huang & Hartemink, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The combined application of organic fertilizer, cattle manure, and biochar has advantages for better crop production (Zhang et al, 2020). The application of compost significantly increased N and K uptake and decreased soil pH, EC, and SAR, while increasing bulb yields of shallot (Rahayu, Saidi, et al, 2020;Syamsiyah et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of biochar can significantly increase the soil pH at a level of a = 5%. According to Rahayu et al (2019), shell biochar with a pH of around 10 can neutralize acidic soil pH. The increase in soil pH due to the application of biochar may be due to the release of alkaline cations (Nurida et al, 2015).…”
Section: Soil Characteristicsmentioning
confidence: 99%
“…The results showed that shell biochar dose had a significant effect (α = 5%) on the fresh green onion weight. According to Rahayu et al (2019), coconut shell biochar can hold nutrients in the soil so that it helps plants to absorb nutrients in the soil which can then increase plant fresh weight. The results of our study showed that the effect of biochar dose on the yield of fresh stover was not very strong.…”
Section: Weight Of Fresh and Air-dried Bulbsmentioning
confidence: 99%